Normal Values for Transbulbar Sonography and Magnetic Resonance Imaging of the Optic Nerve Sheath Diameter (ONSD) in Children and Adolescents - Steinborn, M.; Friedmann, M.; Hahn, H.; Hapfelmeier, A.; Macdonald, E.; Warncke, K.; Saleh, A. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Purpose: To establish normal values of the optic nerve sheath diameter (ONSD) in children and adolescents for transbulbar sonography and magnetic resonance imaging.Materials and Methods: In 99 children and adolescents (age: 5.6 – 18.6 years, mean: 12 years) without neurologic or ophthalmologic disease, measurements of the ONSD with transbulbar sonography were performed. For comparison 59 children and adolescents (age: 5.1 – 17.4 years, mean 12.3 years) with a normal MR examination of the brain had measurements of the ONSD on a T2-weighted thin section sequence of the orbit. Besides establishing modality-related normal values, age dependency, accuracy and reproducibility of measurements were assessed.Results: Overall the mean ONSD was 5.75 ± 0.52 mm for transbulbar sonography and 5.69 ± 0.31 mm for MRI. There was no statistical significance between the 95 % percentiles and age for both transbulbar sonography (p = 0.332) and MRI (p = 0.336). As a parameter for the reproducibility of measurements, the repeatability coefficient (RC) was between 0.34 mm and 0.46 mm. The concordance correlation coefficient (CCC) values revealed a high agreement between readers both for transbulbar sonography (0.868) and MRI (0.796).Conclusion: Normal values for ONSD in children and adolescents found in this study are significantly higher than assumed. The values found for transbulbar sonography are confirmed by comparable results for MR measurements. A precise sonographic measurement technique and the consideration of normal values found hereby are essential for correct interpretation of ONSD measurements in children and adolescents.
Keywords: eye; MR imaging; ultrasound